Blob eaudiobook A love story. - Su, Maggie (HarperAudio, 2025)
"There is so much at play in this wondrous novel. Vi, struggling to place herself in any context that makes sense within the world, earnestly leads us into a wild experiment, to turn a blob into the man of her dreams, and I was transfixed by her voice. This is a book that looks at identity and desire in profoundly interesting ways." — Kevin Wilson, bestselling author of Now Is Not the Time to Panic A humorous and deeply moving debut novel in the vein of Bunny and Convenience Store Woman about a young woman who tries to shape a sentient blob into her perfect boyfriend. The daughter of a Taiwanese father and white mother, Vi Liu has never quite fit into her Midwestern college town. Aimless after getting dumped by her boyfriend and dropping out of college, Vi works at the front desk of a hotel where she greets guests, refills cucumber water samovars, and tries to evade her bubbly blond coworker, Rachel. Little does Vi know her life is about to be permanently transformed when she agrees to a night out with Rachel. In the alley outside the bar, Vi discovers a strange blob—a small living creature with beady black eyes. In a moment of concern and drunken desperation, she takes it home. But the blob is no ordinary pet. Becoming increasingly sentient, it begins to grow, shift shape, and obey Vi's commands. As the entity continues to change, Vi is struck with a daring idea: she'll mold the creature into her ideal partner. Feeding it a stream of sweet breakfast cereals and American pop culture, the creature grows into a movie-star handsome white man. But when Vi's desire to be loved unconditionally threatens to spiral out of control, she is forced to confront her lonely childhood, her aloof ex-boyfriend, and the racial marginalization that has defined her relationships—a journey of self-discovery that teaches her it's impossible to control those you love. Blending the familiar with the surreal, Blob is a witty, heartfelt story about the search for love and self and what it means to be human.